A Comparative Analysis Of Environmental Accounting Initiatives In Ghana And Nigeria - Oti, Peter A.; Egbai, Emmanuel O.; Otalor, John I. (Archives of Business Research, 2019)
The global world continues to suffer the detrimental effect of water and air pollution on marine life and human health. The government desire to change the situation depends on their initiatives towards stemming the tide, and in recent years some developing nations such as Nigeria and Ghana have taken some initiatives to effect this change by promoting the performance of environmental accounting reporting framework. The issues have been that of enforcement and compliance and of creating accounting systems that will give both firms and their stakeholders a clear perspective on the total environmental effect of firms. This study used trend analysis to assess the impact of carbon emission, greenhouse gas, nitrogen oxide and methane emission on the ecosystem in Nigeria and Ghana, and the accounting initiatives thereof. Data were sourced from the World Development Indicators. The findings from the study indicate that environmental accounting initiative is significant in benchmarking standards for corporate reporting. It is recommended from the findings that; there should be harmonized global environmental accounting reporting initiatives, which will serve as benchmark for global reporting on environment. The governments of Nigeria and Ghana should step-up enlightenment programmes on policies and laws on environmental protection in order to increase awareness amongst corporations operating in the two countries. Also, the relevant agencies should ensure enforcement and compliance with these policies and laws.